Improving Outcomes of Posterior Approach Levatorpexy for Congenital Ptosis With Reduced Levator Function. Issue 5 (September 2018) - Feldman, Ilan; Brusasco, Lucas; Malhotra, Raman
Abstract : Purpose: The authors present a new series of our experience using posterior approach levatorpexy for congenital ptosis with poorer levator function (LF) in comparison with our first published report. This technique avoids a skin incision or any resection in addition to no excision of tissue. Methods: A consecutive series of 16 patients. Retrospective review of levatorpexy for congenital ptosis. Data included eyelid margin reflex distance 1, pretarsal show, contour, and complications, including nocturnal lagophthalmos, eyelid lag on downgaze, and dry eye. Surgery was considered successful if the following 4 criteria were simultaneously met: a postoperative margin reflex distance 1 of ≥2 mm and ⩽4.5 mm, intereyelid height asymmetry of ⩽1 mm, no overcorrection compare to opposite eye, and satisfactory eyelid contour. Results: Mean age was 10.3 years (range 1–26 years). Mean LF was 7.3 mm (2–14 mm), while 66% (12) had LF ⩽7 mm. Preoperative phenylephrine test was positive in 87.5% of patients. Mean preoperative and postoperative margin reflex distance 1 was 1.34 mm and 3.2 mm, respectively. Fourteen patients (87%) achieved the desired eyelid height and fulfilled our criteria set of success. Among 10 patients with LF ⩽7 mm, 9 (90%) achieved the desired eyelid height and fulfilled our criteria set of success. Ninety-four percent did not report nocturnal lagophthalmos. Three patients needed a further levatorpexy procedure due to undercorrection. Mean postoperative follow up was up 11.2 (range 6–36) months. Conclusions: Posterior approach levatorpexy is an useful first-line choice for congenital ptosis for all ranges of LF. It is popular among parents due to its avoidance of a skin incision or any resection or excision of tissue. Abstract : The authors report encouraging results in patients with congenital ptosis with reduced levator function. Using a posterior approach technique that not only avoids a skin incision but also requires resect or excise tissue.